Facebook for dummies - Abram, Carolyn; Pearlman, Leah (For dummies, 2010)
"Open the book and find: steps for finding and connecting with friends on Facebook; tips for choosing who should be your Facebook friend and who shouldn?t; privacy controls and how to set them; how to build a profile for a business, artist, or cause; what photo tags are and why to use them; how to find groups you?d like to join; steps for finding friends using your e-mail address book; how friend lists simplify communication and privacy"--P. [4] of cover